Application of Autologous Mesenchymal Stem Cells in Various Diseases: A Systematic Review - hariaji, ilham (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract:The use of mesenchymal stem cells (MSCs) to cure various diseases has become more widespread. Various clinical trials have been reported, both at level 1 and level 4. This systematic literature study aims to find out what diseases have been treated with autologous mesenchymal stem cells.This study is a systematic literature study by conducting literature searches in national and international journals in the last five years using the Google Scholar application using a systematic study method with the help of prism diagrams and classification tables to facilitate search.From the search results, 24 papers were obtained that were included in the inclusion criteria. The results of this study found that the use of MSCs as an alternative in the treatment of diseases has been very much carried out in clinical trials, where most of the results of these studies show a good level of safety, and can provide improvements histologically and physiologically, although in some diseases further research must be carried out to obtain consistent results.Keywords: Mesenchymal Stem Cells, MSCs, Autologous